Analysis of CPF policy changes : new interest rates policy and investment restrictions - Cai, Janice Qina (2008)
This report analyses the impact of the CPF policy changes announced in the National Day Rally 2007. In particular, it looks into the effect of interest rate changes and investment restrictions on a CPF member's total balance. In addition, the observed changes and trends in the demographic of income and age will be discussed.